Sensing of 0.1 ppm of methanol, ethanol, and propanol vapors at 130°C by SnO2 thin film. (4th May 2017) - Choudhury, Sandip Paul; Bhattacharjee, Ayon
ABSTRACT: SnO2 thin film was synthesized by spray pyrolysis. The sensing properties of the same for detecting volatile organic compounds (VOCs) were investigated. It was observed that the sensing was maximum for methanol vapor (96.82%) in case of both experimental and theoretical results. The gas was detected for as low as 0.08 ppm, which has not been reported till date. The Levenberg–Marquardt (LM) algorithm was used for the theoretical analysis using the Electrochemical Impedance Spectroscopy (EIS) Spectrum analyzer. Theoretical calculation revealed that the resistance due to the grain boundary reduces when gases were introduced into the chamber.